ANALISIS PENDAPATAN USAHATANI KAKAO (Theobroma cacao L.) DI DESA SAITI KECAMATAN NUHON KABUPATEN BANGGAI - Hairul Umam; Yuni Rustiawati; Trianto Enteding (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2026)
Cocoa (Theobroma cacao L) is one of Indonesia's plantation commodities that plays an important role in the national and local economies by increasing the income of every business actor. This study aims to determine the income of cocoa farming in Saiti Village, Nuhon District, Banggai Regency. This study used a quantitative method based on a population of 125 people. From this number, a simple random sampling technique was used, whereby each sample was selected at random to represent each sample engaged in cocoa farming. The number of samples taken was 25% of the population, resulting in a sample size of 25 people. Based on the results of the study, it can be concluded that the average income of farmers during the harvest season in one year is Rp. 31,898,959/ha, and this income is obtained from the total farmers' income of Rp. 35,360,000/ha minus the total cost of Rp. 3,461,041/ha. The results obtained indicate that cocoa farming is feasible because it is profitable